1987
DOI: 10.1099/0022-1317-68-9-2461
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Androgens on Paralysis in Mice Following Intravenous Inoculation of Herpes Simplex Virus

Abstract: SUMMARYIn mice, intravenous inoculation of relatively avirulent strains of herpes simplex virus [e.g. P2C6, a mutant of strain CL(101), deficient in thymidine kinase] produced infection in the adrenal gland and mid-spinal cord followed by hind limb paralysis without death. Male mice were less susceptible to paralysis than female mice. Castration of male mice before inoculation increased their susceptibility to that of female animals; treatment with testosterone reversed this change. The differences in suscepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
1

Year Published

1988
1988
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 9 publications
0
14
1
Order By: Relevance
“…This finding agrees with studies showingthat HSV-1-specific antibodies are generally more abundant in female mice than in male mice-a difference that disappears upon castration (22). Some authors have also reported HSV-1-infected males to have less severe clinical disease (17,39). Yirrell et al (39) showed that male mice were less susceptible to paralysis than female mice and that castration prior to infection increased the probability of disease in males to that in females; treatment with testosterone reversed this change.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…This finding agrees with studies showingthat HSV-1-specific antibodies are generally more abundant in female mice than in male mice-a difference that disappears upon castration (22). Some authors have also reported HSV-1-infected males to have less severe clinical disease (17,39). Yirrell et al (39) showed that male mice were less susceptible to paralysis than female mice and that castration prior to infection increased the probability of disease in males to that in females; treatment with testosterone reversed this change.…”
Section: Discussionmentioning
confidence: 98%
“…Some authors have also reported HSV-1-infected males to have less severe clinical disease (17,39). Yirrell et al (39) showed that male mice were less susceptible to paralysis than female mice and that castration prior to infection increased the probability of disease in males to that in females; treatment with testosterone reversed this change. On the contrary, Han et al (14) showed that after infection with HSV-1 by corneal scarification, mortality and reactivation were more common in males.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Females are also disproportionately afflicted by autoimmune disease, such as lupus erythematosus, rheumatoid arthritis, myasthenia gravis, scleroderma, Sjögren's syndrome, multiple sclerosis, experimental allergic encephalomyelitis (EAE) (10,28,36), and herpes simplex virus (HSV). Despite early reports of differences in antibody titer (22) and severity of paralysis after HSV-1 inoculation of mice (18,38), gender-based differences in HSV-1 infection or in HSV-1-associated diseases have not been well studied.…”
mentioning
confidence: 99%
“…This suggests that androgen receptors can overcome whatever mechanisms or regulations the apoE imposes on the transgenic mouse harboring the human ε 4 allele. Yirrell et al (1987) reported that androgens offered protection against systemic HSV-1 infection in mice. 4) Endosomal trafficking (endocytosis) and lipid rafts have been suggested by us (Hill et al, 2004) as playing a role in anterograde and retrograde transport of HSV.…”
Section: Apoe Isoform-dependent Effects and Hormones (Estrogens And Amentioning
confidence: 99%